Identification of Potential PDE5 Inhibitors from Natural Sources for Erectile Dysfunction Therapy Through A Molecular Docking Approach - Mantiri, Vic; Tendean, Lydia; Turalaki, Grace (Universitas Sam Ratulangi, 2025)
The global prevalence of erectile dysfunction has increased in recent decades, and despite various treatment modalities, including phosphodiesterase-5 (PDE5) inhibitors, side effects and contraindications necessitate alternative therapies. This research explores the potential of active compounds present in aphrodisiac plants as PDE5 inhibitors using a molecular docking approach. Eight test compounds evaluated, namely quercitrin, quercetin, garcinoic acid, ellagic acid, catechin, and kaempferol, exhibited high affinity towards PDE5. Receptor-ligand analysis revealed interacting residues supporting PDE5 inhibition. Pharmacokinetic analysis demonstrated similarities, particularly in terms of bioavailability and toxicity, among these ligands, except for quercitrin when compared to the control ligand, sildenafil. This study found that compounds derived from herbal sources show potential as PDE5 inhibitors, with pharmacokinetic profiles comparable to sildenafil. Experimental validation is required to verify the efficacy of these ligands.